(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2019)
تهدف الدراسة إلى إلقاء الضوء على واقع استخدام نظم المعلومات الإدارية في جودة عملية صنع القرار الإداري في بنك الإسكان للتجارة والتمويل، وأيضا من اجل اكتشاف المشاكل والصعوبات التي تؤثر في عملية اتخاذ القرارات، كما تحاول الدراسة درجة، ودور نظم المعلومات الإداريه في جودة اتخاذ القرارات في البنك. ومن أبرز النتائج التي تم الوصول إليها التأكيد على الارتباط الوثيق بين نظم المعلومات الإدارية وعملية جودة صنع القرارات الإدارية و الأثر الكبير لنظم المعلومات الإدارية في جودة صنع القرار الإداري من حيث ( البعد الزمني، والبعد الشكلي، المحتوى). This study aimed to shed light on the real use of management information systems (MIS) in decision making in the housing bank for trade & finance, then to see the difficulties and problems that affect the decision making process in the bank. The study tries to assess the degree of the role of (MIS) in decision making quality in the housing bank for trade & finance. After analyzing the data, the following results were found. There is a significant correlation between (MIS) and decision making regarding the proper kinds of decision and a significant correlation between (MIS) and decision-making regarding the efficiency dimensions (Time, Form, and Content).